Evaluating Malaria Prevalence Using Clinical Diagnosis Compared with Microscopy and Rapid Diagnostic Tests in a Tertiary Healthcare Facility in Rivers State, Nigeria - M. N. Wogu; F. O. Nduka (Journal of Tropical Medicine)
The World Health Organization’s policy on laboratory test of all suspected malaria cases before treatment has not yielded significant effects in several rural areas of Sub-Saharan Africa due to inadequate diagnostic infrastructure, leading to high morbidity and mortality rates. A cross-sectional randomized study was conducted to evaluate the validity of clinical malaria diagnosis through comparison with microscopy and rapid diagnostic test kits (RDTs) using 1000 consenting outpatients of a tertiary hospital in Nigeria. Physicians conducted clinical diagnosis, and blood samples were collected through venous procedure and analyzed for malaria parasites using Giemsa microscopy and RDT kits. Microscopy was considered the diagnostic “gold standard” and all data obtained were statistically analyzed using Chi-square test with a P value <0.05 considered significant. Malaria prevalence values of 20.1%, 43.1%, and 29.7% were obtained for clinical diagnosis, microscopy, and RDTs, respectively (P<0.05). Values of 47.2%, 95.9%, and 77.8% were obtained for sensitivity, specificity, and diagnostic accuracy, respectively, in clinical diagnosis, while RDTs had sensitivity, specificity, and diagnostic accuracy values of 73.7%, 97.3%, and 88.3%, respectively, when compared to microscopy (P<0.05). Clinical diagnosed malaria cases should be confirmed with a parasite-based laboratory diagnosis and more qualitative research is needed to explore why clinicians still use clinical diagnosis despite reported cases of its ineffectiveness.